Supply chain finance: a literature review. Issue 4 (3rd May 2016) - Gelsomino, Luca Mattia; Mangiaracina, Riccardo; Perego, Alessandro; Tumino, Angela
Abstract : Purpose: – The purpose of this paper is twofold: to classify the research to-date on supply chain finance (SCF) according to the main themes and methods, and to propose directions for future research. Design/methodology/approach: – The review is based on 119 papers mainly published from 2000 to 2014 in international peer-reviewed journals and in the proceedings of international conferences. Findings: – The articles that provide a definition of SCF reflect two major perspectives: the "finance oriented" perspective – focused on short-term solutions provided by financial institutions, addressing accounts payable and receivable – and the "supply chain oriented" perspective – which might not involve a financial institution, and is focused on working capital optimisation in terms of accounts payable, receivable, inventories, and sometimes even on fixed asset financing. Research limitations/implications: – While efforts were made to be all-inclusive, significant research efforts may have been inadvertently omitted. However, the authors believe that this review is an accurate representation of the body of research on SCF published during the specified time frame, and feel that confidence may be placed on the resulting assessments. Originality/value: – The paper presents a comprehensive summary of previous research on this topic and identifies the most important issues that need to be addressed in future research. On the basis of the identified gaps in the literature, four key issues have been highlighted which should be addressed in future research.